The origin and organization of the bee colony Apis mellifera L. - Eskov, Eugeney (Cambridge Scholars Publisher, 2019)
The book examines original information on the honey bee's adaptation to a wide range of environmental factors, which have enabled it to adapt to life on all continents inhabited by humans. It shows that the origin of the bee colony is associated with its transformation into an integral biological unit, subjected to the action of natural selection, and explains the contradiction between the eurythermia of the bee colony and the stochasticity of a single member of it. -- Provided by publisher